GAYA BAHASA DALAM ARTIKEL SEPAK BOLA DI UC NEWS APP MEDIA BOLASPORT - Fajaruddin, Ridho; Hermandra, Hermandra; Charlina, Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The style of language is a way that is done by someone in conveying information with beautiful language, both spoken and written language in order to achieve a good impression to the listener or reader. The purpose of this study is to describe the style of language that occurs and the dominant usage in football articles in UC News APP media BolaSport. Data collected gradually a day of 5 articles for seven days. That is, the entire article that became the source of research data as much as 35 articles. In this study, the authors use descriptive method, the steps ranging from data collection, classify, analyze, and make conclusions to get a picture of the object under study. Technique of data collecting conducted in this research is documentation. Result of research, found 9 form of language style from 71 data collected. The language style consists of 2 antonomasia language styles, 8 hyperbolic language styles, 10 parraphic language styles, 6 rhetorical language styles, 5 sinekdoke language styles, 22 metaphorical language styles, 4 personific style languages, 13 symbolic language styles, and 1 trophic style. Overall, the style of the metaphor language is the dominant language style of its use in football articles on UC News APP BolaSport media.Keywords: style of leanguage, football, article, Uc News